Rugby Passing Test Instruments: Validity and Reliability in the Indonesian Version - Tri Nur Faidah; Erick Burhaein (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Accuracy is the key to success in passing rugby. Rugby accuracy tests have been developed and applied for a long time in western countries. However, its application in Indonesia only imitates previous tests by the country without validation and reliability tests. Therefore, the purpose of this study is to find out whether the measuring tool for rugby passing accuracy is suitable for use in the sport of rugby for athletes in Indonesia. The research was carried out by carrying out an accuracy test on 30 participants and then the results were processed and analyzed using IBM SPSS 26. This study uses a quantitative method to identify the results of the validity and reliability data of accuracy test instruments. The data analysis technique used Pearson correlation and Cronbach alpha indicator on IBM SPSS 26. Based on the results of the validity test, the results of Pearson correlation analysis with 30 athletes were declared valid, namely 0.703 > 0.361 and reliable with a Cronbach's alpha value of 0.810. Thus, the instrument can be declared suitable for use as a measuring tool in the research data collection process.